Caracterização estratigráfica, química e mineralógica do massará e conflitos socioambientais associados a sua exploração em Teresina, PI, Brasil - Bartira Araujo da Silva Viana (2013)
The main objective of this research is the characterization of the layers where massará occurs, its stratigraphic, physical, chemical and mineralogical aspects, highlighting its genesis and spatialization in the city of Teresina and its surroundings, as well as environmental conflicts associated with this mineral activity. The specific objectives of this research were: a) to draw hypotheses about the genesis of stratification of mascara; b) to analyze physically, chemically and mineralogically different layers where massará occurs in the northern and southern areas of Teresina; and c) to characterize the environmental conflicts associated with massará mineral activities. As the basis of the research, different bibliographic sources on the subject and on the overlay of geological, geomorphological, and hypsometric maps and drainage were used, and also maps of land utilization and expansion and of urban sprawl were used in order to build a vectors map of spatial trends of Teresina. Additionally, some field work was conducted, in areas where this material is removed for construction, aiming at observing, photographing and analyzing the different impacts and environmental conflicts associated with this anthropic activity. Therefore, the work followed these assumptions: a) the sediments that compose massará have specific chemical and mineralogical characteristics that make them favorable for being used in construction. b) Materials mining for construction carried out in Teresina has economic and social importance, but it also causes environmental conflicts, due to environmental degradation and mangling of the local landscape. It has been observed that the occurrence of layers with massará are identified inseverals pots around the city, appearing as surface coverage on the top of low plateaus that, in some areas of the city, form topographic divisors of the Parnaiba and Poti rivers, in altimetric quotas which exceed 100m; there for e, most of the time, very far away from the current plains and fluvial terraces of these rivers. It has also been confirmed the presence of portions of sedimentary rocks, which undergo processes of weathering in sedimentary layers present in extractive areas of massará. Thus, this sediment is configured as the alteration mantle and not as deposits resulting from the current fluvial dynamics. The understanding the granulometric characteristics of two stratigraphic profiles with layers of massará common in Teresina, and the specific chemical and mineralogical properties sought to determine their binding qualities. The analysis of the samples of the stratigraphic profiles studied (P1 and P2) revealed that the granulometric distribution, though varying between layers, appears with similar distribution patterns. In general terms, in layers with massará, there is apredominance of sandy textures. The highest clay percentage occurs in layers with "mud". The quartz pebbles found in the profiles have a high degree of rounding and are commonly flattened, being matte and polished. In the samples, the sand fraction shows the highest peaks of quartz (SiO2). In the clay fraction, the predominant element is kaolinite (Al2Si2O5(OH)4). The analyses also determined the occurrence of impurities, such as hematite and magnetite, and that iron oxides, evening a low percentage, are responsible for the reddish color of massará. The variation of titanium, along the layers, showed that the lithological discontinuities present in the stratigraphic profiles studied are large. It has been detected, in smaller proportions, the presence of carbonates (soluble salts) such as thermonatrita (Na2CO3H2O), trona (NaH(CO3)2.2H2O) and natrita (Na2CO3). These may be associated with evaporites from the Parnaiba basin. The laboratory analyses results failed to find out the major elements that could influence the binding of massará; however, they made it possible to identify the chemical differences, from the groupings that separate the elements present in the clay of the components of massará, as well as the lithological discontinuities which exist in the stratigraphic profiles studied. That said, the use of this mineral resource, as a material for the construction industry, is in the dominant presence of kaolinite, in the clay fraction, and of quartz, in the sand fraction, and in its performance as a fine aggregate (replacing the fine sand), but also as a binding composite (cementing), replacing the hydrated lime. It has been detected, however, that the extraction of massará and pebbles in Teresina has generated several environmental impacts, which are clearly visible in the urban landscape, especially in the direction of the space vectors of northern and southern growth of the city, as well as in the western vector, in Timon (MA). The positive impacts have a socioeconomic nature and are related to the generation of employment and income and for supplying the city with low cost materials, essential for construction. The negative impacts are represented by environmental changes, such as air and water pollution, noise and vibrations, visual impacts and environmental discomfort. Conflicts derived from the irregular use of the soil, from the depreciation of neighboring properties, and from the generation of degraded areas also occur, contributing to erosive processes, landslides and falling blocks from the slopes of the hills, besides the inconvenience brought to the urban traffic. Thus, the impacts of mining are related to the high degree of urban occupation, which are exacerbated, due to theproximity of mined and inhabited areas. Such impacts exist because of the government inefficiency, as a normalizing, supervising and managing organ of legal and environmental issues related to the use and occupation of urban landing. For this reason, the possibility of mining exploration in the capital of Piauí is increasingly limited, due to a disorganized and predatory extraction of these natural resources and also to the horizontal expansion of the city, i.e., the construction of large housing projects by the government or private enterprises, such as luxurious condominiums. Irregular building, through illegal occupation of villages or slums, and other forms of landing use and occupation, also contributes to this problem, making perspectives of guarantee of future supplies random and preventing a sustainable mining activity.